Drag Coefficient Constraints for Space Weather Observations in the Upper Thermosphere - Valerie Bernstein; Marcin Pilinski (Space Weather)
Abstract The space weather research community relies heavily on thermospheric density data to understand long‐term thermospheric variability, construct assimilative, empirical, and semiempirical global atmospheric models and validate model performance. One of the challenges in resolving accurate thermospheric density data sets from satellite orbital drag measurements is modeling appropriate physical aerodynamic drag force coefficients. The drag coefficient may change throughout the thermosphere due to model dependencies on composition and altitude. As such, existing drag coefficient model errors and corresponding errors in orbit‐derived density data sets and models may be altitude and solar cycle dependent with greater errors at higher altitudes around 500 km near the oxygen‐to‐helium transition region. In this paper, inter‐satellite observed‐to‐modeled density comparisons at ∼500 km are evaluated to constrain drag coefficient modeling assumptions. Observed densities are derived from accelerometer data for the Gravity Recovery and Climate Experiment (GRACE) satellites and Two‐Line Element data for a set of compact satellites, while the NRLMSISE‐00 atmospheric model is used to obtain modeled densities and composition information. Density consistency results indicate that drag coefficient models with incomplete energy and momentum accommodation produce the most consistent densities, while the standard diffuse modeling approach may not be appropriate at these altitudes. Models with momentum accommodation between 0.5 and 0.9 and energy accommodation between 0.83 and 0.96 may be most appropriate at upper thermospheric altitudes. Modeling drag coefficients with diffuse gas‐surface interactions for the GRACE satellites could lead to errors in derived density of ∼25% and in‐track satellite orbit prediction uncertainty during solar maximum conditions on the order of kilometers.